Faktor Penyebab Ketidakmampuan Mahasiswa dalam Pengelolaan Kelas pada Mahasiswa PLK PAI UNP Periode Juli–Desember 2024 - Nasution, Abdul Rahim; Rivauzi, Ahmad (Lembaga Yasin AlSys, 2025)
This study aims to describe the factors contributing to students’ difficulties in classroom management during the Praktik Lapangan Kependidikan (PLK), a phenomenon that significantly impacts the effectiveness of teaching and the readiness of pre-service teachers in real classroom settings. The objective is to investigate the challenges faced by students of the Islamic Religious Education (PAI) Study Program at Universitas Negeri Padang (UNP) in fulfilling pedagogical, professional, personal, and social competencies during the PLK period of July–December 2024. This research employed a qualitative case study approach, involving participants selected through purposive sampling based on their experiences in managing classroom-related challenges. Data were collected through preliminary questionnaires, structured interviews, and documentation, and analyzed using the Miles and Huberman model. The findings reveal both internal and external barriers affecting the four core areas of teacher competence. Internal barriers include limited understanding of student characteristics, difficulties in applying theory to practice, low communication and motivational skills, and weaknesses in classroom management and learning assessment. External barriers include limited preparation time, insufficient practical coursework, lack of professional guidance, restricted access to ICT, and challenges in school adaptation and collaboration. The study concludes that a reformulation of PLK preparation and mentoring strategies is essential to strengthen students’ professional readiness. The implications include the need to enhance practice-oriented curriculum, improve field supervision quality, and develop training grounded in real classroom contexts to foster comprehensive competence among novice teachers.